Arteriovenous malformation of the prostatic median lobe: a rare case treated by transurethral resection - Ibrahim Untan (Journal of the Pakistan Medical Association, 2023)
Arteriovenous malformation localised to the prostate is rare. Until recently, the gold standard for diagnosis was angiography; however, this changed with the use of computed tomography and magnetic resonance imaging, which quickly became the first-line diagnostic tools. Common complaints are haematuria and lower urinary tract symptoms, for which there are no well-defined management guidelines. We present the case of a 53-year-old male patient who was treated for clotted haematuria. While the bleeding was thought to originate from an enlarged prostate, cystoscopy displayed a non-pulsatile, exophytic, active bleeding mass on the median lobe. The mass was resected transurethrally and diagnosed as arteriovenous malformation. This case shows an aberrant presentation of a vascular malformation in the prostate. The mass seemed to be constrained to a compact area without a visible plurality of arterial feeders. Since the prostate is a rare location for arteriovenous malformation, there are no well-defined treatment options. ---Continue